Efeitos da anexina1 na isquemia e reperfusão renal: estudo funcional e histopatológico em modelo experimental - Facio Júnior, Fernando Nestor (2006)
The aim of the present study was to investigate the effects of the use of the anti-inflammatory protein annexin 1 (Anx-A1), which is found in most cells. It is characterized by its ability in binding to calcium and phospholipids, conferring protection against the initial effects of ischemia-reperfusion injury. Right nephrectomy was performed on 48 adult males Wistar rat, with sizes ranging between 250-300 g, maintained on a diet normosodic , normoprotein and with water ad libitum. The animals was divided into 3 groups: Annexin-1/Ischemia (Anx-A1-I/R) (n=16), vehicle (PBS40)-Ischemia (Vehicle-I/R) (n=16) and Sham Group (n=16). The endovenous administration of Anx-A1 was made 30 minutes before ischemia of the left renal artery. The animals of each group were divided and studied at 2 and 7 days post-reperfusion, in respect to the glomerular, tubular and renal structure functions. The results showed that there was a reduction in the glomerular filtration rate (GFR) in the Vehicle-I/R Groups at 2 and 7 days post-reperfusion (0.42 ± 0.02 mL/min-100g and 0.48 ± 0.05 mL/min-100g, respectively). There was a significantly greater filtration rate in the Anx-A1-I/R Groups compared to the Vehicle-I/R Groups (0.86 ± 0.05 mL/min-100g and 0.73 ± 0.04 mL/min-100g, respectively). A significant difference between the Anx-A1-I/R and Sham Groups (p-value < 0.01) was also observed (7days). The fractional sodium excretion (FeNa) was significantly higher in the Vehicle-I/R Groups when compared to the Anx-A1-I/R and Sham Groups on the 2nd and 7th post-perfusion days. On the 2nd day of the study, the fractional sodium excretion was 0.17 ± 0.01% for the Anx-A1-I/R, 0.42 ± 0.03% for the Vehicle-I/R and 0.21 ± 0.01% for the Sham groups (p-value < 0.001). On the 7th day, the values were 0.27 ± 0.03%, 0.52 ± 0.03% and 0.29 ± 0.01%, respectively (p-value < 0.001). The potassium excretion fraction (FeK) on the 2nd and 7th post-perfusion days did not differentiate between the Anx-A1-I/R and Sham Groups, but it was significantly higher in the Vehicle-I/R Groups. The urinary-plasmatic osmolality ratio (U/Posm) showed a significant reduction in the Vehicle-I/R Groups after 2 and 7 days when compared with the Anx-A1-I/R and Sham Groups. A histopathologic evaluation of renal cortex samples, taken on the 2nd and 7th post-perfusion days, revealed a significant increase in the intravascular and transmigrated neutrophils in ischemic areas of the Vehicle-I/R Groups. Additionally, high rates of transmigrated neutrophils were identified in the ischemia-reperfusion areas of samples of renal medulla from the Vehicle-I/R Group taken on the 2nd and 7th days. There was a significant reduction of the neutrophil transmigration in samples of renal medulla on the 2nd and 7th post-perfusion days in the Anx-A1-I/R Groups, as well as a lower intravascular neutrophil rate. On the 2nd and 7th post-perfusion days, the Sham Group presented with structures of distal and proximal convoluted tubules and well-preserved brush-border structures in the renal cortex and medulla samples as seen by light microscopy. Similar results were evidenced in the Anx-A1-I/R Groups with preserved structures in the tubules, basal membrane and glomeruli. In the Vehicle-IR Groups, numerous monocytes, cellular debris inside proximal convoluted tubules, dilated capillaries and alterations in the basal membrane structure were seen. These results suggest that the administration of annexin-1 thirty minutes before renal ischemia in rat , prevents the transmigration of neutrophils and confers protection against the initial effects of ischemia-reperfusion injury, as well as providing protection to the glomerular, tubular and renal structure functions.